PELAKSANAAN MANUAL TRAKSI DAN ISOMETRIK EXERCISE TERHADAP PENINGKATAN AKTIVITAS FUNGSIONAL PADA PENDERITA OSTEOARTHRITIS KNEE DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Sabirin Berampu; Timbul Siahaan; Isidorus Jehaman; Samuel Ginting; Duwi Mekarsari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Osteoarthritis is a chronic degenerative disorder that primarily affects the articular cartilage of the synovial joint, and ultimately bone and remodeling (spurs) at the joint boundary occur. Synovial thickening and capsule progression and joint effusion also occur. Disorders due to Osteoarthritis cause limited activity and limited ability in activities. Because, damage to the cartilage (cartilage) of the joint, so that the thickness of the subcondral bone increases, sclerosis of the bone plate, the growth of osteophytes in the joints, can stretch the joint capsule, resulting in inflammation, and weakening of the muscles connecting the joints. This study aimed to determine the effect of Manual Traction and Isometric Exercise in patients with Knee Osteoarthritis at Grandmed Lubuk Pakam Hospital. Using quasi experiments with one group pretest posttest with a sample of 19 respondents. Measurement of Functional Activity with Jette Scale, using paired sample t-test analysis. There is a significant influence on functional activities before and after. hypothesis test by paired sample t-test obtained with the results of p-value < Î± (0.001 <0.05). There is the Effect of Manual Traction and Isometric Exercise on Functional Activity Enhancement in Patients with Knee Osteoarthritis at Grandmed Lubuk Pakam Hospital. Researchers suggest that the next researcher add a number of samples and a longer time so that the results obtained are more maximal.